Facile synthesis and characterisations of novel Mn-1,2,4-triazole framework (UPMOF-4) as a promising electrode material for supercapattery device - Raman, Velan; Gándara, Felipe; Azman, Nur Hawa Nabilah; Mohamed Tahir, Mohamed Ibrahim; Abdul Rahman, Mohd Basyaruddin; Sulaiman, Yusran (Elsevier, 2023)
A novel porous Mn-based metal-organic framework (MOF) was solvothermally synthesised from the combination of 1,2,4-triazole (Htrz) and Mn(II) ions with the aid of N, N′-dimethylacetamide (DMA). For the first time, the prepared manganese-1,2,4-triazolate framework denoted as MnCl(C2N3H2)(C4H9NO) = MnCltrzDMA, UPMOF-4 was used as an electrode in the assembly of supercapattery device. The UPMOF-4 impressively demonstrated a decent specific capacity of 203.1C/g at 0.4 A/g in a three-electrode configuration by displaying a battery-graded nature. The UPMOF-4 was then sandwiched with activated carbon (negative electrode) to fabricate a supercapattery device. This device demonstrated a specific capacity of 174.96C/g at 0.4 A/g with a specific energy of 32.97 Wh/kg at a specific power of 542.86 W/kg. The assembled device portrayed promising capacity retention of 78.2 % after 10,000 cycles. The favourable electrochemical performance is imputed to the structural stability and the porous nature of UPMOF-4.